Influence of the factors of the aviation enterprise’s management environment on the safety of aviation activity - Шмельова, Тетяна Федорівна; Сікірда, Юлія Володимирівна; Ассаул, Олексій Юрійович (Technology audit and production reserves, 2015)
International Civil Aviation Organization (ІСАО) requires further improvement based on the risk assessment methods which focused on further quantity reduction of aviation accidents in the world. The modern approach gives us an opportunity to verify different objects and subjects of aviation as a single system. For this reason, today, it is very important to investigate the combined influence of inhomogeneous factors of internal and external management environment of aviation enterprise on the aviation safety and to identify all the risk factors. The structural analysis of management environment of aviation enterprise was carried out. And, as follows it from the analysis, inhomogeneous factors which influence the aviation activity were classified and formalized: – factors of internal management environment of aviation enterprise (goals, tasks, structures, technology and personnel); – factors of external management environment of aviation enterprise of direct influence (consumers, competitors, partners, laws and authorities) – factors of external management environment of aviation enterprise of indirect influence (economic situation, progress in science and technology, political factors, sociocultural factors, international events). Hierarchic composition of priorities is based on the example of «Technology» – factor of internal management environment of aviation enterprise. Set-theoretical approach was suggested in order to generalize the inhomogeneous factors of management environment of aviation enterprise. It allows to take into account structural hierarchical pattern, inhomogeneity, dynamic instability and to define conditions for their estimation. The variables of significance were obtained with the help of expert estimation. The variables show the influence of parameters of factors of internal and external management environment on aviation safety. It was determined that the aircraft performance characteristics among the parameters of factor of internal management environment «Technology» have the greatest influence. The level of vehicles, buildings and constructions dilapidation as well as technological operations on airport servicing have the lowest influence. The value of multiplicative function of estimation of parameters of factor of internal management environment «Technology» was obtained while aviation enterprise examination. Estimation method of influence of inhomogeneous factors of management environment of aviation security will be applied to the «Passports of aviation safety». The passport will be used by the State Aviation Service of Ukraine for the quantative evaluation during audits aviation companies.